Long term treatment efficacy & complications of hypofractionated stereotactic radiosurgery in brain arteriovenous malformations. (December 2020) - Tam, Aurora K.Y.; Chan, David Y.C.; Lim, Kevin; Poon, Darren; Kam, Michael; Cheung, Michael; Wong, George K.C.
Highlights: Hypofractionated stereotactic radiosurgery can be applicable for cerebral AVM. AVM Score predicts obliteration rate and morbidity. Index irradiated drainage vein volume is associated with survival and rebleeding. Abstract: Objective: To evaluate long term treatment efficacy and complications of hypofractionated stereotactic radiosurgery (hfSRS) and identify factors that predict outcomes. Methods: A retrospective review was conducted on 34 consecutive patients who received hfSRS from 2008 to 2017. Demographic, clinical, angio-architectural characteristics, and radiosurgery data were extracted from the Clinical Data Analysis and Reporting System and our unit's iPlan (BrainLAB, Munich) system. Data was analysed using SPSS. Results: 5-year obliteration rate was 39.1%. Most patients (n = 29, 85.3%) recovered well with GOS of 4–5. 26.9% (n = 9) patients have at least one post-radiosurgery complication including hemorrhage, neurological deficits, radionecrosis. Neurological morbidity and mortality was 17.6% (n = 6). A higher modified radiosurgery arteriovenous malformation score (mRBAS) is associated with a lower 5-year obliteration rate (Rho = -0.486, p = 0.025). None of the bAVM were obliterated once mRBAS exceeds 5.35. As expected, a larger 20-Gy volume outside lesion is associated with more complications and poorer GOS. Interestingly, irradiated drainage vein volume indexed to AVM volume (iiDVV) correlates with increased risks of post-hfSRS haemorrhage (Rho = 0.472, p = 0.031) and reduced event-free survival (Rho = −0.472, p = 0.031). Once iiDVV exceeds 20%, a high rebleeding rate after hfSRS is anticipated (AUC under ROC 0.889). Conclusion: Hypofractionated stereotactic radiosurgery is an alternative radiosurgery treatment for bAVM unsuitable for single-fraction SRS. mRBAS predicts obliteration rate and morbidity in hfSRS. Index irradiated drainage vein volume (iiDVV) is associated with event-free survival and rebleeding and should be minimized if feasible.